Examining Job Complexity on Job Crafting Within Conservation of Resources Theory: A Dual-Path Mediation Model - Bai, Jing Yi; Tian, Qing; Liu, Xia (Frontiers in Psychology, 2021)
This study examined the different ways in which job complexity influences employees’ job crafting. Specifically, we draw on conservation of resources (COR) theory to hypothesize that job complexity is positively related to approach crafting via work engagement (i.e., resource gain process). At the same time, job complexity may also induce employees to engage in avoidance crafting (i.e., resource loss process) as employee energy resources are depleted. Our data consists of 251 employees working in Macau. We used structural equation modelling (SEM) in Mplus software to test the proposed hypotheses. Our findings confirm that job complexity has differential effects on approach and avoidance crafting through work engagement and energy depletion. These findings highlight the importance of costs and benefits of job complexity and the importance of resources in the employees’ job crafting process. We discuss the practical implications for modern organizations in which complex jobs are prevalent.